2020
DOI: 10.3390/jpm10040146
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comorbidities on SARS-CoV-2 Viral Entry-Related Genes

Abstract: Viral entry mechanisms for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are an important aspect of virulence. Proposed mechanisms involve host cell membrane-bound angiotensin-converting enzyme 2 (ACE2), type II transmembrane serine proteases (TTSPs), such as transmembrane serine protease isoform 2 (TMPRSS2), lysosomal endopeptidase Cathepsin L (CTSL), subtilisin-like proprotein peptidase furin (FURIN), and even potentially membrane bound heparan sulfate proteoglycans. The distribution and expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Animal models indicate that ACE2 and Ang-(1-7) are protective in asthma ( El-Hashim et al, 2012 ). In recent studies, ACE2 expression was not altered ( Breidenbach et al, 2020 ; G. Li et al, 2020 ; Peters et al, 2020 ; Radzikowska et al, 2020 ) or reduced ( Jackson et al, 2020 ; Kimura et al, 2020 ) in asthmatic patients; but increased expression of TMPRSS2, the enzyme facilitating SARS-CoV-2 entry into host cells, has been reported ( Kimura et al, 2020 ; Radzikowska et al, 2020 ). However, in a large cohort study, increased ACE2 gene expression was reported in a sub-group of type 2 asthmatic patients ( Camiolo, Gauthier, Kaminski, Ray, & Wenzel, 2020 ).…”
Section: Corticosteroids Non-steroid Anti-inflammatory Drugs and Acmentioning
confidence: 98%
“…Animal models indicate that ACE2 and Ang-(1-7) are protective in asthma ( El-Hashim et al, 2012 ). In recent studies, ACE2 expression was not altered ( Breidenbach et al, 2020 ; G. Li et al, 2020 ; Peters et al, 2020 ; Radzikowska et al, 2020 ) or reduced ( Jackson et al, 2020 ; Kimura et al, 2020 ) in asthmatic patients; but increased expression of TMPRSS2, the enzyme facilitating SARS-CoV-2 entry into host cells, has been reported ( Kimura et al, 2020 ; Radzikowska et al, 2020 ). However, in a large cohort study, increased ACE2 gene expression was reported in a sub-group of type 2 asthmatic patients ( Camiolo, Gauthier, Kaminski, Ray, & Wenzel, 2020 ).…”
Section: Corticosteroids Non-steroid Anti-inflammatory Drugs and Acmentioning
confidence: 98%
“…Different cardiovascular complications, such as myocarditis, acute coronary syndrome, decompensated heart failure, pulmonary embolism, cardiogenic shock, and infection of a heart transplant recipient, accompanied by altered levels of creatine kinase isoenzyme-MB, myohemoglobin, cardiac troponin I, and N-terminal pro-brain natriuretic peptide were currently reported ( 1 , 149 155 ). In addition, a high prevalence of pre-existing cardiovascular morbidities, including hypertension, and coronary artery diseases, has been detected among patients with severe SARS-CoV-2 ( 1 , 149 , 156 ). In COVID-19 patients, the highest mortality rates were also observed in case of pre-existing cardiovascular disease and elevated cardiac troponin levels ( 137 , 157 ).…”
Section: Sars-cov-2 Clinical Implication and Potential Mutual Interacmentioning
confidence: 99%
“…SARS-CoV-2 entry of host cells could involve host cell membrane-bound angiotensin-converting enzyme 2 (ACE2), transmembrane serine protease isoform 2 (TMPRSS2), lysosomal endopeptidase cathepsin L, and membrane bound heparan sulphate proteoglycans (HSPGs) and others [ 21 ]. As the receptor for SARS-CoV-2, ACE2 is present on the surface of lung alveolar epithelial cells, enterocytes of the small intestine, renal tubules, heart, arterial and venous endothelial cells, arterial smooth muscle cells, cerebral neurons and monocytes/macrophages [ 22 , 23 ].…”
Section: Pathogenesis Of Covid-19mentioning
confidence: 99%
“…Among patients with diabetes and CV disease, the expression levels of TMPRSS2 are elevated significantly in comparison to healthy individuals. Additionally, expression of viral entry-related genes is increased in the settings of hypertension across target organ systems [ 21 ]. Thus, if infected by the virus, these patients may have higher risk of CV complications and progression to critically-ill condition.…”
Section: Covid-19 and CV Complicationsmentioning
confidence: 99%